Business ethics research in the hospitality industry: topics, methods and trends. (2017) - Sehitoglu, Yasin; Ross, Gary; Köseoglu, Mehmet Ali
This study investigates how business ethics research has evolved in hospitality management (HM). This evolution is explored using bibliometrics from articles related to ethics published in HM journals indexed in SSCI. This study provides a broad view on ethics research in HM related to topics discussed, methods employed, and trends. As a first study of HM with a business ethics focus, the findings show several things. First, there has been a significant increase in the number of such articles. Second, the most popular topics are corporate social responsibility and natural environmental issues. Third, quantitative methods and primary data provided by hotels are dominant in many studies; qualitative, hybrid research approaches, and advanced statistical methods have become more common in recent years. Accordingly, referring to the findings related to this study, this article presents limitations of the study and future steps.